The Effect of Work Motivation and Job Satisfaction Through Employee Engagement on Employee Performance - Nurhidayat, Wahid Ahmad; Siti Mariam (International Journal of Economics (IJEC), 2025)
This study aims to determine the relationship between Work Motivation and Job Satisfaction on Employee Performance at Bank XYZ mediated by Employee Engagement. The research method used is quantitative with descriptive design, respondents were selected through purposive sampling. Data were collected using Google Form and analyzed using SEM PLS. The results showed that Work Motivation has a positive and significant effect on Employee Engagement and Employee Performance. Then Job Satisfaction is proven to have a positive effect on Employee Engagement and Employee Performance. In addition, there are results of the mediation hypothesis, namely mediating Employee Engagement, Work Motivation and Job Satisfaction on Employee Performance. This study supports all the hypotheses proposed and is consistent with previous studies, emphasizing the importance of Work Motivation, Job Satisfaction and Employee Engagement in influencing Employee Performance both directly and through mediation. The managerial implications of these findings include the need to focus on improving Employee Work Motivation at Bank XYZ must be given more attention and improved so that Employee Engagement can be even better in the future. Research limitations include covering samples that are limited to the West Jakarta area and do not group employee income. Further research is suggested to expand the scope of the sample and can add other variables that are relevant to the novelty of the research